Childhood Vascular Tumors - Hinen, Harriet Bagnal; Boccuto, Luigi; Trenor, Cameron C.; Wine Lee, Lara (Frontiers in Pediatrics, 2020)
Vascular tumors in pediatric patients are an important entity for the clinician to recognize and correctly diagnose. They may present at birth or develop at any point during infancy, childhood, or adolescence. Most are benign, but even benign lesions may have significant morbidity without proper intervention. Malignant vascular tumors are also rarely seen in the pediatric population, and may be associated with various syndromes.